The Role of Legal Philosophy in the Protection Women From Violence - Oktavian, Ivan Danara; Rasji, Rasji (Budapest International Research and Critics University, 2021)
This paper aims to examine how the development of an integrated criminal justice system in handling cases of violence against women and the role of legal philosophy in it. This research is normative legal research. This study concludes that the Continental European legal system influences the legal system in Indonesia, so procedural law is an administration of justice that provides guidelines for the working of the institutions involved in the adjudication process. Gender equality during the drafting of the Criminal Procedure Code has not yet become an important issue. This has an impact on the absence of an article formulation in the Criminal Procedure Code that accommodates the special interests of women dealing with the law, both as perpetrators and victims, especially women as victims of gender-based violence, even though many women who are victims of gender-based violence generally experience trauma from the events they experience. The concept of an Integrated Criminal Justice System for Handling Cases of Violence against Women (SPPT-PKKTP) was built as an effort to support the state to be able to carry out its constitutional obligations to fulfill women's human rights in conflict with the law, especially women who are victims of gender-based violence. Considering that the operation of the Criminal Justice System (SPP) is generally regulated based on the Criminal Procedure Code, to present the SPPT-PKKTP so that the criminal justice procedure law becomes a victim perspective, advocating the SPPT-PKKTP concept into the Draft Amendment to the Criminal Procedure Code is something that needs to be done. Philosophy of law is the basic foundation of legal science; it can explain that legal philosophy greatly protects the role of human rights, which guarantees the protection of women.